The beta2-adrenergic agonist salbutamol is a potent suppressor of established collagen-induced arthritis: mechanisms of action. - Malfait, A; Malik, A; Marinova-Mutafchieva, L; Butler, D; Maini, R; Feldmann, M (1999)
The therapeutic potential of salbutamol, a beta2-adrenergic agonist, was explored in collagen-induced arthritis. This study was based on a report that salbutamol, by elevating intracellular cAMP, inhibits IL-12 production by macrophages and dendritic cells, thus preventing Th1 development. Ten-week-old male DBA/1 mice were immunized by intradermal injection of type II collagen in CFA. Arthritis developed 15-30 days later and the mice were treated after onset of disease with salbutamol, 200 microgram i.p. After 10 days, the mice were sacrificed, and the hind paws were evaluated histologically. Salbutamol, 200 microgram daily or every other day, had a profound therapeutic effect on the clinical progression of arthritis, as assessed by clinical score and paw thickness. The therapeutic effect was dose dependent. Daily administration of 200 microgram of salbutamol offered the best protection against joint damage, as assessed by histology. In vitro, salbutamol reduced IL-12 and TNF-alpha release by peritoneal macrophages in a dose-dependent manner, as well as TNF release by synovial cells from arthritic mice. Ex vivo, draining lymph node cells of the salbutamol-treated arthritic mice showed a diminished CII-specific IFN-gamma production and proliferation. In vivo, salbutamol specifically blocked mast cell degranulation in joint tissues. In conclusion, salbutamol has important effects on the immunoinflammatory response and a significant therapeutic action in collagen-induced arthritis.